2014
DOI: 10.1177/0268355514557854
|View full text |Cite
|
Sign up to set email alerts
|

Chronic venous leg ulcers: Effects of foam sclerotherapy on healing and recurrence

Abstract: This study affirms the role of ultrasound-guided foam sclerotherapy as a safe and effective option for abolition of superficial reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…According to Grover et al, in a sample of 50 limbs with a median follow-up time of 15.2 months, there was recurrence in 4/50 (8%) at 12 months. 19 The partial and total recanalization rates observed in the present study were 26% and 21%, respectively. In some aspects these results are similar to those reported by Howard et al, 18 who observed complete recanalization in 27% and partial recanalization in 58%.…”
Section: Discussionsupporting
confidence: 49%
“…According to Grover et al, in a sample of 50 limbs with a median follow-up time of 15.2 months, there was recurrence in 4/50 (8%) at 12 months. 19 The partial and total recanalization rates observed in the present study were 26% and 21%, respectively. In some aspects these results are similar to those reported by Howard et al, 18 who observed complete recanalization in 27% and partial recanalization in 58%.…”
Section: Discussionsupporting
confidence: 49%
“…26 Abolition of venous reflux performed by UGFS also promotes ulcer healing. 27,28 Deep venous reflux is the main risk factor for delayed healing, according to the present multivariate analysis. Ulcer size and duration, claimed to be other main determinants of healing time, 29 are also important negative prognostic factors in the present case series, together with PAOD.…”
Section: Discussionmentioning
confidence: 52%
“…[ 9 13 ] Emerging evidence of several randomized controlled trials (RCTs) published in recent years suggests a benefit of SF in patients with VLUs. [ 14 16 ] A prospective randomized study from Kulkarni et al [ 17 ] shows that SF agents can significantly improve the healing rate of VLUs and reduce the recurrence rate of VLUs. Another study showed that correction of superficial venous reflux in the lower limbs can help the healing of venous ulcers in the lower limbs.…”
Section: Introductionmentioning
confidence: 99%